Look at the time: diel variation in the flight initiation distance of a nectarivorous bird - Ferguson, Stephen; Gilson, Lauren; Bateman, Bill (SPRINGER, 2019)
Abstract: When approached by a predator, foraging animals should adjust escape behavior based on their current energetic status to minimize opportunity costs (foraging time) and maximize the chance of escape. Animals should therefore be more reluctant to leave a foraging patch when their energy reserves are low and should flee using low-energy escape tactics, but be quicker to flee and use the best escape tactic when satiated. Nectarivorous birds have little capacity for energy storage; thus, they should be particularly sensitive to variation in nutritional status throughout the day. We tested whether New Holland honeyeaters (Phylidonyris novaehollandiae) alter their antipredator behavior by testing whether flight initiation distance (FID—the distance at which an individual flees from an approaching predator) and escape tactic (hopping or flying) vary over the course of the day. Honeyeater FID was shortest in the morning, following the overnight fast, and longest at midday. In the evening, though FID tended to shorten, responses were more variable overall, likely due to individual variation in foraging success. In the morning, honeyeaters were equally likely to hop or fly when approached, but increasingly favored flight as the day progressed. These results suggest a strong link between individual energetic condition and antipredator responses. We suggest that time of day is a useful and important variable influencing escape behavior, the potential effects of which should be more consistently considered as a covariate in the widely used FID protocol. Significance statement: Diel variation in internal and external conditions can alter behavioral responses. In this study, we observed antipredator response behaviors in foraging New Holland honeyeaters, small passerines sensitive to changes in energy status throughout the day. We found that honeyeaters allowed researchers to approach more closely in the morning and evening before fleeing and escaped by flying more often than hopping as the day progressed. Our results suggest that antipredator behaviors are sensitive to current energy status and impending energy needs. In addition, we show that time of day is an important consideration in the experimental design and statistical analysis of behavior studies.